(untitled) (Eurasian Journal of Religious Studies, 2017)
This article is published under the project «Features of missionary activity in the Republic of Kazakhstan». The article analyzes the initial stages of the Christianization of the Russian Empire policy. Politics of Russian missionary associated with the creation of the Russian state and the beginning of colonial policy. For the Russian Empire Christianization policy has been a source of ownership of non-Russian nationalities. Christianization played a major role in the loss of national identity and the Russification of non-Russian peoples. The adoption of Orthodox subjects of the Russian Empire, influenced by the work of tireless missionaries. In the policy of the Christianization pursued by the Russian Orthodox Church, there has been coercion and manipulation. The article refers to the Christianization of the peoples of Siberia and the Far East, Volga and Transbaikalia.